Molecular Mechanisms Regulating the Dendritic Development of Newborn Olfactory Bulb Interneurons in a Sensory Experience-Dependent Manner - Yoshihara, Sei-ichi; Takahashi, Hiroo; Tsuboi, Akio (Frontiers in Neuroscience, 2016)
Inhibitory interneurons in the olfactory bulb are generated continuously throughout life in the subventricular zone and differentiate into periglomerular and granule cells. Neural circuits that undergo reorganization by newborn olfactory bulb interneurons are necessary for odor detection, odor discrimination, olfactory memory, and innate olfactory responses. Although sensory experience has been shown to regulate development in a variety of species and in various structures, including the retina, cortex, and hippocampus, little is known about how sensory experience regulates the dendritic development of newborn olfactory bulb interneurons. Recent studies revealed that the 5T4 oncofetal trophoblast glycoprotein and the neuronal Per/Arnt/Sim domain protein 4 (Npas4) transcription factor regulate dendritic branching and dendritic spine formation, respectively, in olfactory bulb interneurons. Here, we summarize the molecular mechanisms that underlie the sensory input-dependent development of newborn interneurons and the formation of functional neural circuitry in the olfactory bulb.